Integrated Single-Stage Converters with Tri-State Modulation Suitable for Photovoltaic Systems - Galotto, Luigi [UNESP]; Brito, Moacyr A. G. de [UNESP]; Sampaio, Leonardo P. [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2011)
The aim of this work is to present two topological simplified converters named Tri-state Boost and Tri-state Buck-Boost integrated single-phase inverters. An important operation capability can be achieved for these converters using a Tri-state Modulation control scheme. This is the inductive power decoupling and the independent input output control. These features are directly related with the photovoltaic micro-converter needs, improving efficiency, cost and mainly lifetime. These features for the proposed modulation are confirmed through experimental results.
Keywords: Integrated converter; Single-Stage converters; Tri-State Modulation; Power Decoupling; Photovoltaic Systems